PELATIHAN MENULIS SIMPLE PRESENT TENSE MENGGUNAKAN SHORT STORY DI YOUTUBE UNTUK REMAJA RPTRA KALIDERES - Baiatun Nisa; Sulhizah Wulan Sari; Leny Hikmah Rentiana; Paramita Kusumawardhani (Jurnal Bakti Masyarakat Indonesia, 2023)
The simple present tense is one of the tenses that must be understood by every English learner. However, learningthe simple present tense is not easy because there are differences in the verb depending on the subject of thesentence. Therefore, the English study program at Bina Sarana Informatics University held a Simple Present TenseWriting Training Using Short Stories on YouTube for RPTRA Kalideres Youth. The result of the situational analysisis that the teenagers at RPTRA Kalideres have difficulties in using verbs. This can happen because the use of theverb depends on the subject of the sentence. Therefore, the purpose of this community service is to make it easier forteenagers to understand and use the simple present tense through short stories on YouTube. The method used in thisactivity is the PAR (Participatory Action Research) method in which teenagers do simple present tense exercisesthrough short stories on YouTube. Pre-test and post-test were conducted to find out the impact of using short storieson YouTube in learning the simple present tense. The results of using short stories on YouTube provide significantresults in learning the simple present tense. From the results of pre-test and post-test, there are some improvements,they were 10 participants who improved for 5%, 7 participants with 10% improvements, and 3 participants who didnot improve for the results.ABSTRAKSimple present tense adalah salah satu tenses yang wajib dipahami oleh setiap pembelajar bahasa Inggris. Namunmempelajari simple present tense pun bukan hal yang mudah karena adanya perbedaan kata kerja (verb) tergantungpada subjek (subject) kalimatnya. Oleh sebab itu program studi bahasa Inggris Universitas Bina Sarana Informatikamengadakan Pelatihan Menulis Simple Present Tense Menggunakan Short Story di YouTube Untuk Remaja RPTRAKalideres. Hasil dari analisis situasi adalah para remaja di RPTRA Kalideres tersebut memiliki kesulitan dalampenggunaan kata kerja (verb). Hal ini dapat terjadi karena penggunaan kata kerja (verb) tergantung dari subjek(subject) kalimatnya. Oleh sebab itu, tujuan dari pengabdian masyarakat ini adalah untuk mempermudah pararemaja memahami dan menggunakan simple present tense melalui cerita pendek (short story) di YouTube. Metodeyang digunakan dalam kegiatan ini adalah metode PAR (Participatory Action Research) dimana para remajamengerjakan latihan simple present tense melalui cerita pendek (short story) yang ada di YouTube. Pre-test danpost-test dilakukan untuk mengetahui dampak dari penggunaan cerita pendek (short story) di YouTube dalammempelajari simple present tense. Hasil dari penggunaan cerita pendek (short story) di YouTube tersebutmemberikan hasil yang signifikan dalam mempelajari simple present tense. Dengan adanya pre-test dan post-testterlihat adanya peningkatan sebesar 5% untuk 10 peserta, peningkatan 10% untuk 7 peserta, dan 3 peserta tidakmengalami peningkatan hasil atau 0%.